GANGGUAN SPERMATOGENESIS SETELAH PEMBERIAN MONOSODIUM GLUTAMAT PADA MENCIT (MUS MUSCULUS L.) - A.A.SG.A SUKMANINGSIH; I GUSTI AYU MANIK ERMAYANTI; NGURAH INTAN WIRATMINI; NI WAYAN SUDATRI (Jurnal Biologi Udayana, 2011)
This study was conducted to investigate the effect of monosodium glutamate (MSG) on spermatogenesis of male experimental mice.using 32 twelve-week old mice. They were divided randomly into 4 groups, each group consisted of 8 mice. One group was used as control, three groups were used as treatment, which received 1.5 mg/g body weight/day, 3 mg/g body weight/day and 4.5 mg/g body weight/day of MSG solution in destilled water for 35 days. The result showed that MSG treatment led to disturbance on spermatogenesis by reduction in some of the parameter studied. There was a significant (p < 0.05) decrease in the number of pachytene spermatocyte and spermatid 15, where as the decrease in spermatogonia was insignificant (p>0.05).